A Circular Economy Model for ESG-Driven Sustainable Management Practices: Lessons from Community-Based Irrigation Waste Management - Masduki Masduki; Moch. Febri Sayidil Umam; Alan Rusdiana; Anisa Nurul Hidayah (Penerbit Goodwood, 2026)
Purpose: This study examines the role of circular economy implementation in fostering Environmental, Social, and Governance (ESG)-oriented sustainable management practices within community-based irrigation waste management in Indonesia. Research Methodology: A quantitative approach was employed using survey data collected from community members involved in irrigation-waste management activities. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software to evaluate the relationships among circular economy practices, ESG dimensions, and sustainable management practices. Results: The findings indicate that the implementation of a circular economy positively and significantly influences ESG performance and sustainable management practices. In addition, ESG dimensions significantly mediate the relationship between circular economy practices and sustainable management outcomes, demonstrating that ESG strengthens the effectiveness of circular economy implementation at the community level. Conclusions: Integrating circular economy principles with ESG frameworks effectively supports sustainable community-based environmental management practices. ESG serves as an evaluation framework and a strategic mechanism to enhance sustainability outcomes. Limitations: This study was limited by its cross-sectional design and focus on community-based irrigation waste management. Contributions: This study extends the application of ESG from corporate settings to community-based sustainability contexts and offers a replicable model for sustainable environmental management strategies.